Prevalence of psychopathy in a community sample of Spanish adults: Definitions and measurements matter - Sanz-García, Ana; Peña Fernández, María Elena; García-Vera, María Paz; Sanz, Jesús (Frontiers in Psychology, 2022)
The main objective of this work was to examine the prevalence of psychopathy in the general adult population from the main currently existing theoretical perspectives of psychopathy, using for this purpose the five-factor or Big Five model as a common language that allows the comparison and integration of the personality traits considered as defining psychopathy by these different perspectives. The NEO Personality Inventory-Revised (NEO PI-R) was applied to a sample of 682 adults of the general Spanish population. The prevalence of clinical and subclinical psychopathy was calculated according to six different definitions of these two constructs based on Hare’s, Lilienfeld’s, triarchic, and DSM-5-hybrid models, and the simultaneous presence of a minimum number of personality traits that differed from the sample mean by one standard deviation. Prevalence rates for the different definitions were consistently low, indicating that the prevalence of clinical psychopathy in the general Spanish population is around 0.55%, and that of subclinical psychopathy is around 1.65%. There were no significant sex differences in the prevalence of psychopathy. These results question the alarmist claims that warn about the existence in society of a very high number of people with psychopathy who can cause many social, economic, physical, and psychological damage to others.